Arab Gulf Monarchies as an Epistemic (Online) Community Revisited. Diffusion, Competition, and Survival in the Aftermath of the Arab Uprisings. - Schuhn, Laura (Taiwan Journal of Democracy, 2021)
By 2017 at the latest, with that year’s blockade of Qatar driven by the Saudi, Bahraini, Egyptian, and Emirati leaderships, the fragility of the concept of an epistemic community of Arab monarchies, as described by Sean Yom in 2014 in this journal, has come to the fore. In this light, this essay advocates a shift in this concept toward a different type of “discursive formation,” which may advance our understanding of authoritarian clustering in the context of this debate. Taking Twitter as a proxy for an epistemic (online) community, this study analyzes the activities of Gulf elites on the site between 2017 and 2020 and identifies a significant subcluster within the Gulf Cooperation Council (GCC) states consisting of Saudi, Bahraini, and Emirati accounts. Given the context of day-to-day politics, this finding may not surprise us; however, this work suggests that it is not the mere existence of epistemic links resulting from cultural, historical, economic, or structural ties, but rather a convergence in content that drives authoritarian cooperation and the diffusion of legitimation strategies and norms of autocratic practic
Keywords: Authoritarian clustering; authoritarianism; diffusion; GCC; Middle East; monarchies; Twitter